The growth of cassava (Manihot esculenta Crantz) on various alternative gelling agents - DODY PRIADI; HANI FITRIANI; ENNY SUDARMONOWATI (Biodiversitas Journal of Biological Diversity, 2008)
Gelling agents which is an important component in plant tissue culture media is considered expensive which causes high cost of plant micropropagation in developing countries. The objective of the study was to evaluate various commercial starches (hunkue, sago, tapioca, maize and arrowroot) and food agars for substitution of standard technical agar which commonly used in tissue culture medium. Young stem cuttings with five buds of cassava (Manihot esculenta Crantz. genotype Iding and Gebang) cultured on MS hormone-free media solidified with those starches and agars. Parameters observed were total and length of shoots and rate of contamination. Result of studyshowed that the highest total shoots (2.45) on genotype Iding obtained from Agar Swallow 0.8% (control), meanwhile on Gebang (2.85) obtained from tapioca 25%. The highest shoot length on genotype Iding (17.2 mm) obtained from maize, meanwhile on Gebang obtained from agar Sinar Kencana 2% (8.95 mm). Contamination rate of explants caused by bacteria or fungi on genotype Iding was 30-70%, meanwhile on Gebang was 20-60%. Further study needs to be done to evaluate more gelling agents from different sources and theircombinations.Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: medium, gelling agents, agar, starch, cassava (Manihot esculenta Crantz).